Pegembangan Game dengan Menggunakan Teknologi Voice Recognition Berbasis Android - Marpaung, Franky Hadinata; Sutoyo, Rhio; Daniel, Daniel; Yonas, Yonas; Vedro, Vedro (ComTech: Computer, Mathematics and Engineering Applications, 2014)
The purpose of this research is to create a new kind of game by using technology that rarely used in current games. It is developed as an entertainment media and also a social media in which the users can play the games together via multiplayer mode. This research uses Scrum development method since it supports small scaled developer and it supports software increment along the development. Using this game application, the users can play and watch interesting animations by controlling it with their voice, listen the character imitating the users? voice, play various mini games both in single player or multiplayer mode via Bluetooth connection. The conclusion is that game application of My Name is Dug use voice recognition and inter-devices connection as its main features. It also has various mini games that support both single player and multiplayer.